The Implementation of Whole Brain Teaching Method to Improve Students’ Speaking Skill - Alrasyid, Harun (Verba: Journal of Applied Linguistics, 2024)
The purpose of this study is to characterize the ways in which the Whole Brain Teaching (WBT) method improves students’ speaking skill and to ascertain the teacher effectiveness and classroom climate. This classroom action research is conducted for the students of Eleventh Grade of SMK Negeri 2 Surabaya. The research consists of three cycles, The data are collected through speaking test, observation and focus group discussion. Both quantitative and qualitative data were examined by the researcher. According to the findings, students' speaking skills have improved in a few areas. They can now articulate their thoughts clearly, form some sentences using just their own words, and provide accurate answers to questions. Additionally, the environment in the classroom has changed; they are more engaged in adhering to the classroom activities.